Physico-Chemical and Biological Properties of Mn(II), Co(II), Ni(II) and Cu(II) Chelates of Schiff Bases - SANTWANA GAUR, MRS. (Asian Journal of Chemistry, 2010)
Two novel Schiff bases were synthesised using 1-methyI2-pyrro- idinone/1-methyl-2-pyridone with o-phenylene diamine along with their Mn(ll), Co(ll), Ni(II) and Cu(lI) chelates and characterised. The IR, electronic thermogravimetric data, antibacterial and antifungal activities are discussed here.